Amino acid-based anti-fouling functionalization of silica nanoparticles using divinyl sulfone. (August 2016) - Wang, Hanqi; Cheng, Fang; Shen, Wen; Cheng, Gang; Zhao, Jing; Peng, Wei; Qu, Jingping
Graphical abstract: Abstract: Natural amino acids are zwitterionic molecules and the good biocompatibility promises them potential candidates as anti-fouling materials. Here, we developed a new method to functionalize silica nanoparticles with a natural amino acid-based anti-fouling layer. Amino acids were covalently immobilized on 3-aminopropyltriethoxysilane modified silica nanoparticles using divinyl sulfone through a two-step reaction in aqueous solution at room temperature. The progress was monitored with NMR, X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM) and zeta potential measurements. A library of amino acids was screened and the nonspecific protein adsorption of bovine serum albumin (BSA) and fetal bovine serum (FBS) were investigated using dynamic light scattering method. The results showed that cysteine, lysine and arginine functionalized silica nanoparticles can effectively resist protein adsorption due to the zwitterionic structure. Among them, lysine functionalized silica nanoparticles had the best anti-fouling performance, which showed hydrodynamic diameter increases of only 10% after incubated in BSA solution and 20% after incubated in FBS solution for 24 h. The neat aqueous modification process can conveniently create a thin zwitterionic layer on silica particles, and it has a great potential in biomolecule immobilization and biofunctional surface preparation. Statement of Significance: Zwitterionic polymer is an outstanding class of anti-fouling material; but the difficulty in synthesis is challenging its spread utilization. In this study, we developed a new method to create an amino acid-based zwitterionic layer on APTES functionalized silica nanoparticles through a two-step reaction in aqueous solution at room temperature. The surface chemistry was monitored with NMR, XPS, TEM and zeta potential measurements. With this method, a library of amino acid conjugated-silica nanoparticles was synthesized and their anti-fouling performance was evaluated using dynamic light scattering method. The results showed that the cysteine, lysine and arginine conjugated nanoparticles all can effectively resist nonspecific protein adsorption. Among them, lysine conjugated nanoparticles show the best anti-fouling performance, which showed hydrodynamic diameter increases of only 10% after incubated in BSA solution and 20% after incubated in FBS solution for 24 hours. These results indicates that the anti-fouling silica nanoparticles are of great potential in many biomedical applications, especially biosensing and diagnose imaging. The modification reactions in aqueous solution at room temperature are easily conducted in laboratory, indicating high potential in the functionalization of silica particles/surfaces with other biomolecules.